Nucleation and growth controlled reduced graphene oxidesupported palladium electrocatalysts for methanol oxidation reaction - Ng J.C.; Tan C.Y.; Ong B.H.; Matsuda A.; Basirun W.J.; Tan W.K.; Singh R.; Yap B.K. (SAGE Publications Ltd, 2023)
Anodes; Cathodes; Direct methanol fuel cells (DMFC); Electrocatalysts; Electrolysis; Fuel cells; Methanol; Methanol fuels; Nanocatalysts; Nucleation; Oxidation; Palladium; Catalyst nano particles; Catalytic performance; Electrochemical active surface areas; Methanol oxidation reactions; Microwave assisted reduction; Microwave synthesis; Nucleation and growth; Reduced graphene oxides; Graphene